DIFFERENTIAL SENSITIVITY OF NH4+ AND NO2? OXIDATION TO CdCl2 AND AlCl3 IN AN AQUEOUS SYSTEM (Journal of Sciences, Islamic Republic of Iran)
The effects of different concentrations of CdCl2 and AlCl3 on NH4+ and NO2? oxidation in an aqueous system were investigated. AlCl3 had no effect on NH4+ removal and its oxidation to NO2?, whereas NO2? disappearance was greatly enhanced by AlCl3. In contrast, CdCl2 delayed removal of NH4+ and its subsequent oxidation to NO2? and also decreased the rate of NO2? disappearance. When compared to the controls, NO3? production from NH4+ oxidation decreased severely by CdCl2 whereas slight increase in NO3? production was observed in the presence of AlCl3. The results presented provide evidence for differential sensitivity of NH4+ and NO2? oxidation to AlCl3 and CdCl2 in an aquatic environment.